Analysis of factors influencing the physical, chemical and sensorial properties of Serra da Estrela cheeses - Guiné, Raquel (2016)
The objective of this study was to evaluate the chemical, color, textural, and sensorial characteristics of Serra da Estrela cheese and also to identity the factors affecting these properties, namely thistle ecotype, place of production, dairy and maturation. The results demon- strated that the cheeses lost weight mostly during the ﬁrst stage of maturation, which was negatively correlated with moisture content, being this also observed for fat and protein contents. During maturation the cheeses became darker and with a yellowish coloration. A strong corre- lation was found between ash and chlorides contents, being the last directly related to the added salt in the manufacturing process. The ﬂesh ﬁrmness showed a strong positive correlation with the rind harness and the ﬁrmness of inner paste. Stickiness was strongly related with all the other textural properties being indicative of the creamy nature of the paste. Adhesiveness was posi- tively correlated with moisture content and negatively correlated with maturation time. The trained panelists liked the cheeses, giving high overall assessment scores, but these were not signiﬁcantly correlated with the physicochemical properties. The salt differences between cheeses were not evident for the panelists, which was corroborated by the absence of correlation between the perception of saltiness and the analyzed chlorides con- tents. The Factorial Analysis of the chemical and physical properties evidenced that they could be explained by two factors, one associated to the texture and the color and the other associated with the chemical properties. Finally, there was a clear inﬂuence of the thistle ecotype, place of production and dairy factors in the analyzed properties.